Celiaco-Mesenterial Arterial Aberrations in Patients Undergoing Extended Pancreatic Resections: Correlation of CT Angiography with Findings at Surgery - Egorov, Viacheslav I; Yashina, Nina I; Fedorov, Andrey V; Karmazanovsky, Gregory G; Vishnevsky, Vladimir A; Shevchenko, Tatiana V (JOP. Journal of the Pancreas, 2010)
Context It is important to recognize arterial variants in the preoperative planning of extended pancreatic resections. The absence of surgical confirmation of radiological data is a limitation of the majority of angiographic or CT-angiographic studies of celiac and mesenteric arterial anatomy. Objective The purpose of this study was to test the accuracy of CT angiography in delineating the arterial architecture by comparing the resultant 3D images with findings at surgery and determining the frequency of different celiac and mesenteric arterial anatomy variants. Methods Abdominal CT angiographies of 350 patients were performed on a 64- and 256-MDCT scanner prior to major pancreatic or hepatobiliary surgery. Variants of celiac and mesenteric arterial anatomy were documented as 3D reconstructions. Radiological data were compared to operative photographs during extended pancreaticoduodenectomies and extended distal pancreatectomies in 59 cases. Results Only 197 patients (56.3%) had the classic arterial anatomy identified at CT angiography. The most common variants were a replaced or accessory right hepatic artery originating from the superior mesenteric artery (62 cases, 17.7%) and a replaced or accessory left hepatic artery (43 cases, 12.3%) originating from the left gastric artery. According to a comparison with operative photographs, CT angiography demonstrated 100% accuracy in identifying celiac and mesenteric arterial anatomy variants, stenoses, obstructions and aneurysms of the celiac and mesenteric branches, including those which were hemodynamically significant and which influence the choice and sequence of operative procedures. Conclusion The celiac and mesenteric arterial anatomy variants are fairly common and are of great significance in planning extended pancreatic resections. Radiological findings were fully corroborated by operative data, which means that CT angiography is a reliable tool for identifying celiac and mesenteric arterial anatomy aberrations and arterial lesions. Image: Changes in functioning arterial collaterals after celiac trunk stenting.